Produção heteróloga e caracterização de uma beta-glicosidase identificada em sequências metagenômicas de um lago da região amazônica - Balula, Augusto Furio (Universidade Federal de São Carlos, 2017)
Metagenomics studies allow the direct analysis of a genetic material in an environmental sample and when linked to bioinformatics it gives a powerful tool to explore the role of new genes and proteins not studied before. Constant decreases in the quantity of fossil fuels and their effects in the global economy and natural environment has accelerated researches in alternative fuels such as the second generation ethanol, which can be produced by vegetation biomass. However, this process demands previous hydrolysis of the lignocellulolytic material by hydrolytic enzymes to provide fermentable sugar. β-glucosidases are enzymes which plays an important role at the final step of cellulose breakdown to glucose, thus being considered the rate limiting enzyme in this process of biomass degradation. Many β-glucosidases are already known, however there is an interest to find new enzymes which are tolerant to glucose inhibition and which exhibits high activity at lower temperatures. In this study we searched for β-glucosidases (GH1) using sequences from a metagenomics database from rivers and lakes in the Amazon region developed in our laboratory. We found 3 complete open reading frames (ORFs) related to β-glucosidases and one of them was selected to be produced in E.coli in a heterologous way and to be biochemically characterized. The coding sequence of the protein named AmBgl1-LP was cloned in the plasmid pET-28a and produced an enzyme which has a molecular mass of 53,7 kDa. The enzymatic assays showed that the enzyme was active with an optimum pH of 5.5, optimum temperature of 35 °C and had a Ki for glucose of 23 mM. The enzyme does not apparently perform transgycosylation, according to the assays for pNPβGlu substrate. Supposedly, AmBgl1-LP suffers inhibition by pNPβGlu on concentrations higher than 10 mM. The enzyme showed to be capable of hydrolyzing cellobiose, pNPβGal and pNPβFuc. Thus, the enzyme is promising for use in cocktails for degradation of biomass.
Keywords: β-glicosidase; Tolerância à glicose; Metagenoma; Glicosil hidrolases; Expressão recombinante; Transglicosilação; Glucose tolerant; Metagenome; Glycosil hydrolases; Heterologous expression; Transglycosylation; CIENCIAS BIOLOGICAS::GENETICA